2005
DOI: 10.1177/0013124504270787
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Grouping and Student Learning in a High-Needs School

Abstract: The study focused on the impact of flexible grouping on student learning during a period of time in a high-needs school. The study tracked nontransient, below-goal elementary students on multiple literacy assessments during a 5-year flexible grouping implementation. Results showed that the percentage of students attaining mastery increased in 16 of 19 over-time comparisons. Increases in the percentage of students At Mastery ranged from 10% to 57%. The percentage of teachers using flexible grouping on a weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…The data collected from the QRI results showed increases in the percentage of students at mastery on six out of seven comparisons. As for the Writing Prompts assessments, Castle et al (2005) found increases in the percentage of students at mastery in five of the six comparisons. The percentage of students attaining at mastery increased in sixteen out of the nineteen comparisons, and increases ranged anywhere from 10% to 57% throughout the five-year study.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…The data collected from the QRI results showed increases in the percentage of students at mastery on six out of seven comparisons. As for the Writing Prompts assessments, Castle et al (2005) found increases in the percentage of students at mastery in five of the six comparisons. The percentage of students attaining at mastery increased in sixteen out of the nineteen comparisons, and increases ranged anywhere from 10% to 57% throughout the five-year study.…”
mentioning
confidence: 84%
“…Teachers assess students frequently to determine student growth and reassign students to different groups based on their results (Tieso, 2003). This strategy of flexible ability grouping is aimed to meet the fluctuating needs of all learners within a classroom (Castle et al, 2005).…”
Section: Within-class Ability Groupingmentioning
confidence: 99%
See 3 more Smart Citations